2020
DOI: 10.32731/smq.292.062020.04
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Fans’ Willingness to Pay for Team’s Environmental Sustainability Initiatives

Abstract: The current study aims to understand if sport organizations can utilize environmental sustainability (ES) efforts to increase revenue in addition to saving money. To do this, fans of the Philadelphia Eagles were surveyed. Findings indicate fans were willing to pay an average of US$6.50 in the form of a sustainability fee to help the organization implement an environmental initiative. Furthermore, this study found that nearly none of the prevailing thoughts on predictors of fan behavior significantly positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The average WTP for environmental measures is lower than WTP of sport club members for other purposes in previous studies (e.g., [14,16,63]), but close to the amount what sport fans of professional teams are willing to pay for environmental sustainability initiatives [42]. The level of WTP is also similar to existing environmental research within Europe [36].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The average WTP for environmental measures is lower than WTP of sport club members for other purposes in previous studies (e.g., [14,16,63]), but close to the amount what sport fans of professional teams are willing to pay for environmental sustainability initiatives [42]. The level of WTP is also similar to existing environmental research within Europe [36].…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, differences in WTP can result from differences in response formats (open question vs. double dichotomous choice vs. payment card; [63]). On the contrary, different payment vehicles (i.e., extra fee in addition to ticket price in [42] vs. membership fee) did not yield material differences in WTP for similar goods which are both related to protecting the natural environment. Overall, respondents were willing to pay an additional amount of money that is equivalent to 10.6% of their current membership fee.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, whether diving tourists are willing to pay a higher price for sustainable diving offers than for non-sustainable diving offers will be investigated. More recently, based on Trail's [74] "sports fan sustainability behavior" model, Greenhalgh and Drayer [75] demonstrated that fans of sports teams are willing to pay a fee for their team's environmental sustainability initiatives. If this were to apply to dive tourists as well, the question about which characteristics influence such behavior arises again.…”
Section: Authors Environmental Sustainabilitymentioning
confidence: 99%